2008
DOI: 10.1123/mcj.12.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Gait Initiation in Multiple Sclerosis

Abstract: Individuals with multiple sclerosis (MS) often have poor balance control that is especially apparent during dynamic tasks such as gait initiation (GI). The purpose of this study was to investigate how balance symptoms due to MS alter spatiotemporal variables, coordination, and temporal margins within the stability boundary during gait initiation. Twelve women with MS (Expanded Disability Status Scale [EDSS] mean = 4.0, SD = 1.4) and 12 women without MS (control group) initiated gait at their preferred speed. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 29 publications
4
67
0
1
Order By: Relevance
“…In addition, Karst et al [5] found that people with MS had a significantly reduced center of pressure displacement during voluntary leaning and reaching. Consistent with the finding that people with MS can lean less far when standing, it was reported recently that during gait initiation, when one needs to lean forward to displace one's center of mass anteriorly, people with MS displace their center of mass less far and less quickly and get less close to their stability boundaries [18].…”
Section: Limited and Slowed Movement Toward Limits Of Stabilitymentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, Karst et al [5] found that people with MS had a significantly reduced center of pressure displacement during voluntary leaning and reaching. Consistent with the finding that people with MS can lean less far when standing, it was reported recently that during gait initiation, when one needs to lean forward to displace one's center of mass anteriorly, people with MS displace their center of mass less far and less quickly and get less close to their stability boundaries [18].…”
Section: Limited and Slowed Movement Toward Limits Of Stabilitymentioning
confidence: 62%
“…When trying to reach or step, people with MS move less far and less quickly than healthy controls [2,5,11,17,18]. Martin et al [11] found that people with MS had significantly reduced functional reach distance when standing compared with controls.…”
Section: Limited and Slowed Movement Toward Limits Of Stabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…This method provides detailed quantitative measures of kinematic, kinetic, and spatiotemporal parameters of gait and can thus provide information about the mechanisms underlying the gait dysfunction as well as precise spatiotemporal data. This type of gait analysis can be used to identify subtle gait impairments [4] and abnormal postural control strategies [8] not captured by other methods of gait analysis. Because performing 3-D gait analysis requires specialized expensive equipment, is time consuming, and requires highly trained and experienced personnel, this method of gait analysis can be a valuable research tool but it has a limited role in clinical practice.…”
Section: -D Gait Analysismentioning
confidence: 99%
“…Studies show that people with MS have a range of gait abnormalities including decreased step length [3•, 4], decreased cadence [3•, 5], reduced joint motion [4,6,7], and more variability of most gait parameters [7] compared with healthy controls. These abnormalities result in reduced gait speed [3,[5][6][7][8], reduced walking endurance [9], an increased metabolic cost of walking [10], and reduced community mobility [11]. Furthermore, people with MS reduce their walking speed and increase the variability of their gait when they walk while performing a cognitive task more than healthy controls [12], suggesting that they need to devote greater cognitive reserve to walking than do people without MS.…”
Section: Introductionmentioning
confidence: 99%